Maternal factor V Leiden and prothrombin mutations do not seem to contribute to the occurrence of two or more than two consecutive miscarriages in Caucasian patients - Baumann, Kristin; Beuter-Winkler, Petra; Hackethal, Andreas; Strowitzki, Thomas; Toth, Bettina; Bohlmann, Michael K. (American journal of reproductive immunology, 2013)
Background: We analysed the prevalence of the most common hereditary thrombophilia (hTP) - factor V Leiden (FVL) mutation, prothrombin 20210 G>A substitution (PT) - and the 677 C>T replacement in the 5,10-methylenetetrahydrofolate reductase (MTHFR) gene in Caucasian patients with a history of two and more consecutive recurrent miscarriages (RMs) as compared to healthy controls with an identical ethnic background and at least one live birth. Methods A multicenter analysis of three hTP was performed in 641 RM patients identically screened at specialized university centres. Results The study groups consisted of 240 patients with 2 (1) and 401 patients with >2 miscarriages (2) and were compared with 157 controls. There was no significant difference in the prevalence of the hTP between RM patients and controls nor within the two study groups. Subgroup analysis showed that the homozygous MTHFR polymorphism was significantly more prevalent in the study group 2 as compared to study group 1 (13.9 versus 7.9%, P = 0.02). Conclusion In Caucasians, maternal FVL or PT mutations do not seem to contribute to the pathophysiology of RM, irrespective of the number of miscarriages. However, the role of the homozygous MTHFR polymorphism merits further investigation.